Pro-psychotic effects of synthetic cannabinoids: interactions with central dopamine, serotonin, and glutamate systems. (2nd January 2018) - Fantegrossi, William E.; Wilson, Catheryn D.; Berquist, Michael D.
Abstract: An association between marijuana use and schizophrenia has been noted for decades, and the recent emergence of high-efficacy synthetic cannabinoids (SCBs) as drugs of abuse has lead to a growing number of clinical reports of persistent psychotic effects in users of these substances. The mechanisms underlying SCB-elicited pro-psychotic effects is unknown, but given the ubiquitous neuromodulatory functions of the endocannabinoid system, it seems likely that agonist actions at cannabinoid type-1 receptors (CB1Rs) might modulate the functions of other neurotransmitter systems known to be involved in schizophrenia. The present review surveys what is currently known about the interactions of CB1Rs with dopamine, serotonin, and glutamate systems, because all three of those neurotransmitters are well-established in the pathophysiology of schizophrenia and psychosis. Identification of molecular mechanisms underlying the pro-psychotic effects of SCB drugs of abuse may establish certain classes of these substances as particularly dangerous, guiding regulations to control availability of these drugs. Likewise, an understanding of the pharmacological interactions which lead to schizophrenia and psychosis subsequent to SCB exposure might guide the development of novel therapies to treat afflicted users.